INFORMATION WAR AS MEANS OF COMBATTING INTERNATIONAL TERRORISM - Покровська, А.В. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2013)
In the article the main approaches to the interpretation of the concepts of information war and information-psychological operations in modern world policy are considered. On the example of the anti-terroristic activity of the USA, notably – the Iraqi anti-terroristic campaign of 2003, the author tries to examine the way, how the USA realize their strategy of the information-psychological wars in the struggle against international terrorism.